Microbiological, histological, technological, and toxicological preliminary study of dog's canned food - RANTOS (Σ. ΡΑΝΤΟΣ), S.; PANTOULAS (Λ. ΠΑΝΤΟΥΛΑΣ), L.; SARAKATSIANOS (Ι. ΣΑΡΑΚΑΤΣΙΑΝΟΣ), I.; ROZOS (Γ. ΡΟΖΟΣ), G.; PAPAIOANNOU (Ν. ΠAΠΑΪΩΑNNOΥ), N. (Journal of the Hellenic Veterinary Medical Society, 2018)
During this study canned food for dogs of six firms were investigated (42 samples totally). Microbiologically the following parameters were checked: the commercial sterility, the water activity (aw), the pH, the presence of aerobic and anaerobic bacteria after incubation of tins in 25 ° C for 28 days, 32 ° C for 21 days and 55 ' C for 8 days. Histologically, the existence of different kinds of tissues was examined. Technologically Weende's analysis and separation of the tin's content were made. Toxicologically, the concentration of lead and cadmium were countered. The results showed that dog's canned food, in Greece, are supersterillised. Muscular, adipose and connective tissue are used for their production as well as byproducts and soya proteins by some firms. The results of Weende's analysis are in full agreement with the amount of nutriments that they were written on tins' labels.